A Case Report of a Complete Penile and Scrotum Skin Degloving Injury - Dongyu Li; Fang Chen; Chenghao Hu; Jianhua Zhang; Jiani Wu; Yuhui Dongye; Huibin Li (Plastic and Reconstructive Surgery, Global Open, 2018)
Summary:. Male genital injuries are rare and only few of them are total penoscrotal degloving injuries. Though this kind of injury is not life-threatening, it could be psychologically devastating to patients if not treated appropriately. This report presents a case of total male genitalia degloving injury treated by sliding flap and skin graft, assisted by Vacuum Sealing Drainage. Via this therapeutic approach, the injured area was completely healed. Three months after surgery, there were still no scars that affected normal function of male genitalia.This approach, which has never been reported before, yields a satisfactory result for both aesthetic appearance and sexual functions.